2020
DOI: 10.1186/s12886-020-01658-9
|View full text |Cite
|
Sign up to set email alerts
|

Success rates of probing for congenital nasolacrimal duct obstruction at various ages

Abstract: Background Although nasolacrimal duct probing is the standard treatment for congenital nasolacrimal duct obstruction (CNLDO) among children, the optimal timing of this procedure has been a topic of debate. The aim of the study was to analyze the clinical efficacy of nasolacrimal duct probing among patients with CNLDO symptoms at various ages. Methods An 8-year retrospective study involved 2434 patients (3009 eyes), who underwent naso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
0
22
0
2
Order By: Relevance
“…Belirtiler genellikle yaşamın ilk birkaç haftasında ortaya çıkar (1,10). Yaşamın ilk aylarında genellikle kendiliğinden açılan bu tıkanıklık, gerektiğinde hidrostatik basıncı artıracak şekilde yapılan masaj ile, olguların %96 kadarında, yaşamın ilk yılında açılabilmektedir (11)(12)(13)(14).…”
Section: Bulgularunclassified
“…Belirtiler genellikle yaşamın ilk birkaç haftasında ortaya çıkar (1,10). Yaşamın ilk aylarında genellikle kendiliğinden açılan bu tıkanıklık, gerektiğinde hidrostatik basıncı artıracak şekilde yapılan masaj ile, olguların %96 kadarında, yaşamın ilk yılında açılabilmektedir (11)(12)(13)(14).…”
Section: Bulgularunclassified
“…Some authors have suggested that delayed treatment could increase the rate of intervention failure, 13 perhaps because of prolonged inflammation and fibrosis in the lacrimal drainage system. 3 , 5 , 6 , 14 However, some reports have found no age-related reductions in success rate. 12 , 15 , 16 When conservative treatment does not lead to lacrimal duct opening, invasive procedures for CNLDO (eg, probing, balloon dacryocystoplasty, and silicone intubation) are recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital nasolacrimal duct obstruction (CNLDO) is a common cause of epiphora in infants; its prevalence rate of 5% to 20%, 1 , 2 although only 2–6% of affected individuals will need intervention. 3 The pathogenesis of CNLDO most commonly involves an imperforate membrane at the distal end of the nasolacrimal duct (the valve of Hasner). However, in some difficult cases, the pathogenesis may involve bony abnormalities and narrowing of the lacrimal drainage system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital nasolacrimal duct obstruction (CNLDO) is a common disease in newborns and the most common cause of neonatal epiphora (excessive tearing) [ 1 ], [ 2 ]. CNLDO has been reported to occur in 1.75–6% of newborns [ 3 ], [ 4 ].…”
Section: Introductionmentioning
confidence: 99%